G25 Efficacy of a shorter bowel prep regime trialled during constraints from COVID19. (12th September 2022) - Allan, Kathryn; Alomari, Yasmeen; Papadopoulos, Michalis; Devadason, David; Kirkham, Sian; Loganathan, Sabarinathan
Abstract : Background: Bowel preparation remains a significant barrier for patients who need to undergo colonoscopy and is recognised by children as the most difficult aspect of the colonoscopy process. Inadequate bowel preparation can lead to increased procedural times, lower caecal intubation rates, and the need for repeat colonoscopy. Practice across paediatric units providing colonoscopy is not uniform with regard to the total number of days of prep prior a colonoscopy and the agent(s) used. Data comparing a two-day regime vs a shorter one-day regime in children is limited. Restrictions during COVID19 including shielding, need for PCR testing, reduction in theatre capacity led to a re-appraisal of the need for a 2-day bowel prep, which was standard practice until 2020. Aim: To evaluate the efficacy and safety profile of a shorter 1-day bowel prep regime in children undergoing colonoscopy and compare this to a standard 2-day regime. Methods: Data was collected prospectively on patients who were prescribed a one-day regime prior to colonoscopy. The data was then compared with similar data on patients who were prescribed a two-day regime from an audit carried out 1 year prior to the COVID19 pandemic. The one-day regime involved taking a high dose of senna followed by two doses of picolax (dose dependent on age). The two-day regime involved a smaller dose of senna followed by three doses of picolax. Comparison was carried out between the two regimes. Boston Bowel Preparation Scale (BBPS) was used to assess the efficacy of bowel preparation. The maximum score possible for the BBPS is 9, and a score of ≥2 in all 3 segments is considered optimal for colonoscopy. 1 Results: There were 24 patients in the one-day bowel prep group and 19 patients in the two-day group. The mean age of children in the two groups were identical (11.4). The majority of patients in both groups received their bowel preparation at home. The indications for colonoscopy were very similar in both cohorts with IBD and PR bleeding being the most common indications. The median BBPS score in the 2-day regime was 6 and was 7 in the 1-day regime. 67% of patients in the one-day group had a BBPS score ≥2 in all 3 segments compared with only 47% of patients in the two-day group. In each group one procedure could not be completed due to inadequate bowel preparation. Conclusions: The one-day bowel preparation was not inferior to the two-day regime. The higher dose of senna used in the shorter 1-day regime was well tolerated. There appears to be little to gain from a longer bowel prep regime. There are several benefits of the one-day regime such as acceptability by patients, fewer days off school/work, reduced numbers of medication doses, and fewer inpatient hospital days necessary to admit for supervised bowel prep. Reference: Lai EJ, Calderwood AH, Doros G, Fix OK, Jacobson BC. The Boston bowel preparation scale: a valid and reliable instrument for colonoscopy-oriented research. Gastrointestinal Endoscopy 2009;69 (3):620–625.